EVIDENCE FOR HIBBINGITE-KEMPITE SOLID SOLUTION - Saini-Eidukat B.; Rudashevsky N.S.; Polozov A.G. (My University, 1998)
New occurrences of hibbingite, γ-Fe 2 (OH) 3 Cl, have been found associated with platinum-group minerals in the Noril'sk Complex, and with the Korshunovskoye iron ores of the southern Siberian platform. The Norils'k grains, which are up to 0. 6 mm in diameter, are associated with the platinumgroup minerals froodite, cabriite, urvantsevite and with native silver in massive pentlandite–cubanite– chalcopyrite ore. The Korshunovskoye iron ore sample in which hibbingite was found is composed of fine-grained magnetite ore associated with halite. Hibbingite, hematite and silver grains are found in cavities in halite; the reddish-brown hibbingite grains usually occur as encrustations in the cavities. The size of hibbingite and hematite grains is up to 100 µm. Hibbingite from the Noril'sk Complex contains a significant kempite (Mn 2 (OH) 3 Cl) component; in some cases it contains over 50 mol. % Mn. These data suggest that at least a partial solid solution series exists between hibbingite and kempite. All known occurrences of hibbingite represent paragenetically late mineral assemblages. In the case of the Korshunovskoye deposits, the occurrences are associated with highly concentrated hydrothermal brines derived from the Lower Paleozoic saline sediments of the Siberian Platform cover.
Keywords: Paleozoic; Paleozoic; Палеозой